A new superacid hafnium-based metal–organic framework as a highly active heterogeneous catalyst for the synthesis of benzoxazoles under solvent-free conditions. Issue 19 (7th September 2017) - Nguyen, Linh H. T.; Nguyen, The T.; Nguyen, Ha L.; Doan, Tan L. H.; Tran, Phuong Hoang
Abstract : A new superacid Hf-based MOF, termed VNU-11-P-SO4, was used as an efficient heterogeneous catalyst for solvent-free 2-arylbenzoxazole synthesis. Abstract : A new crystalline porous superacid material was prepared by sulfation of a Hf-MOF constructed from a 6-connected Hf node and 1, 3, 5-benzenetricarboxylate. The new superacid MOF with the presence of sulfate groups coordinated to a Hf-oxo cluster as superacid sites was found to be an effective heterogeneous catalyst for solvent-free heterocyclization for benzoxazole synthesis.